2022
DOI: 10.1007/s41742-021-00390-6
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Size-Dependent Filtration Efficiency, Breathability, and Flow Resistance of Face Coverings and Common Household Fabrics Used for Face Masks During the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, the increase in demand for protective equipment caused a global shortage and homemade barrier face coverings were recommended as alternatives. However, filtration performances of homemade face coverings have not been fully evaluated. Test methods in the ASTM standard (F3502-21) were used to evaluate filtration efficiencies (FE) and breathability (pressure drop, Δp) of face coverings and home fabric materials commonly used during the pandemic. Submicron particulates FE was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…In cloth face masks, breathability depends on the kind of fabric and the number of layers used, with more layers providing higher filtration efficiency but less breathability. 21 , 30 Our analysis focused on single-layer cloth face masks, which was the most frequently tested type in the available studies. When focusing on multi-layered masks, cloth masks might perform better than our analysis suggests, meaning that our present assessment of cloth masks represents a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…In cloth face masks, breathability depends on the kind of fabric and the number of layers used, with more layers providing higher filtration efficiency but less breathability. 21 , 30 Our analysis focused on single-layer cloth face masks, which was the most frequently tested type in the available studies. When focusing on multi-layered masks, cloth masks might perform better than our analysis suggests, meaning that our present assessment of cloth masks represents a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that a handmade fabric mask could not filter aerosol sizes between 30 and 600 nm, being only effective at capturing large respiratory droplets [5]. Subsequently, multi-layered structures of woven fabric were introduced to improve the filtration efficiency of materials [6,7]. Four layers of silk fabric could protect against particulate penetration ranging from 10 nm to 6 µm [8].…”
Section: Introductionmentioning
confidence: 99%
“…The government enforced safety regulations that limited the peoples’ access to their professional activities, altering output and, eventually, the economy’s aggregate supply. Furthermore, constraints on free moment caused a reduction in the consumption of commodities, leading to a fall in aggregate demand and a direct impact on the environmental quality (EQ) due to reduced GHG (Muhammad et al 2020 ; Ayodeji et al 2022 ). However, pandemic breakouts have severe environmental repercussions owing to the increased volume of local and clinical waste, which may be hazardous and can spread infections to other society members if not properly managed (Syed et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%